Compressed Brown Algae as a Potential Environmental Enrichment Material in Growing Pigs - Françoise Pol; Adeline Huneau-Salaün; Sarah Gallien; Yannick Ramonet; Nicolas Rose (Animals, 2021)
In barren housing conditions, enrichment materials are given to pigs to improve their welfare. Here, we assessed the suitability of an algae-based cylinder as an enrichment material on the behavioral, physiological, health and productivity welfare indicators of pigs. Algae was compared with metal chains and wood logs. The study involved 444 pigs from two successive batches on one single farm. During the suckling period, half of the pigs received algae and the control pigs received no material. After weaning and until the end of fattening, algae, wood or chains were equally distributed among the pigs. Consumption of algae cylinders was different between pens and between batches. After weaning and during the fattening period, although the results differed between batches, no significant difference was observed in the object manipulations. Salivary cortisol, used as biomarker to measure the stress levels after pig transfers, were similar between the treatments. Enrichment material made from algae had no negative effect on pig health and no effect on performance and body condition. Regarding their characteristics and according to Commission Recommendation (EU) 2016/336 classification, algae cylinders can be categorized as suboptimal enrichment materials, although the present results suggest that it does not significantly improve pig welfare compared to a metal chain, which is categorized as a material of marginal interest.